2013
DOI: 10.1097/der.0b013e318280cbe5
|View full text |Cite
|
Sign up to set email alerts
|

Drug- and Virus- or Bacteria-induced Exanthems

Abstract: Finally, DIE and VBIE have distinct skin cytokine profile (IL-5 alone or in combination with granzyme B and perforin in DIEs was statistically more frequent than in VBIEs, mainly when skin biopsy was carried out within 2 days from clinical onset), which might be helpful in discriminating the etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Although blood tests are not routinely performed in our current clinical practice for exanthema or urticaria, it has been recently suggested that some tests could be helpful to distinguish between viral-and drug-induced skin eruptions. As an example, Hari Y et al have shown that in viral exanthemas, IFN-γ is increased in most serum samples from different acute viral diseases, while in drug-induced exanthemas, IL-5 alone or in combination with granzyme B and perforin are often found to be increasedtogether with some eosinophilia (Hari et al, 1999;Bellini et al, 2013). Another example is the potential role of thymus and activation-regulated chemokine (TARC/CCL17) which plays an important in TH2 immune responses.…”
Section: Role Of Virus In Benign Nonimmediate Reaction Viral Infection As a Differential Diagnosismentioning
confidence: 99%
“…Although blood tests are not routinely performed in our current clinical practice for exanthema or urticaria, it has been recently suggested that some tests could be helpful to distinguish between viral-and drug-induced skin eruptions. As an example, Hari Y et al have shown that in viral exanthemas, IFN-γ is increased in most serum samples from different acute viral diseases, while in drug-induced exanthemas, IL-5 alone or in combination with granzyme B and perforin are often found to be increasedtogether with some eosinophilia (Hari et al, 1999;Bellini et al, 2013). Another example is the potential role of thymus and activation-regulated chemokine (TARC/CCL17) which plays an important in TH2 immune responses.…”
Section: Role Of Virus In Benign Nonimmediate Reaction Viral Infection As a Differential Diagnosismentioning
confidence: 99%